Analisis Permintaan Ayam Potong di Pasar Empat Pajak Rebo Kabupaten Deli Serdang - Nadya Haryanti; Susi Apriliani; Bintang Akbar Azhari; Juliana Nasution (VISA: Journal of Vision and Ideas, 2023)
This study aims to analyze the factors that influence the demand for chicken meat in the Pasar Empat Tax Rebo. The research method used is a case study method, namely research that is used by looking directly into the field. And factors that influence the demand for free-range chicken, education level, number of dependents and income level are real factors in the influence of demand on free range chicken. Consumer consumtion patterns of free-range chicken in a month an average of average 3-4 kg a month. Keywords: Market, Hole Elasticity